A Tangle of Gold - Moriarty, Jaclyn (New York, NY : Arthur A. Levine Books, an imprint of Scholastic Inc., 2016)
In Cambridge, England, Madeleine Tully is still working to gather the Royal Family, and get them back to their parallel world--but in Cello, Elliot Baranski is being held captive, the Hostiles are working against the Royal Family, and the World Severance Unit is trying to stop all contact between Cello and the World for good.
Keywords: Magic -- Juvenile fiction; Missing persons -- Juvenile fiction; Royal houses -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Colors -- Juvenile fiction; Magic -- Fiction; Missing persons -- Fiction; Kings, queens, rulers, etc -- Fiction; Interpersonal relations -- Fiction; Color -- Fiction; Fantasy; Cambridge (England) -- Juvenile fiction; Cambridge (England) -- Fiction; England -- Fiction; Young adult fiction; Fantasy fiction